Africa 2050: Urbanization. (January 2014) - Racki, Jeffrey; Patel, Praful; DeGroot, David
The fast-evolving process of urbanization will transform Africa's future. Urbanization can be harnessed to build an effective urban platform for the continent's social and economic development, but this requires the right policies to capture the benefits of urban growth. The scope and scale of urban growth requires a fundamentally different approach to the current practice of making sporadic, large-scale infrastructure investments. Cities must be enabled to facilitate and finance ongoing investment programs, in partnership with local businesses and communities. This article puts forward an agenda for achieving the 2050 vision that focuses on unlocking a more systematic approach to urban development and management. This requires the development of new partnerships for urban development and management, between tiers of government, with the private sector and citizens. It requires a greater focus on using local resources to leverage the financing needed to support urban growth. And it requires strengthened capacity for city planning and management to meet projected demand for land and services. National governments will need to play a leading role in repositioning and strengthening local city managers to meet the challenges of urban growth.